Radial Gate Hydraulic Modelling Of Sultan Abu Bakar DAM, Cameron Highland - Lani, Anuar Effendy Mat (Universiti Sains Malaysia, 2017)
The main objective for this study is to determine discharge coefficient and to developed a discharged rating curve for individual gate, combination of two gates and all radial gates from physical model of Sultan Abu Bakar Dam, Cameron Highland, Pahang. The physical model of Sultan Abu Bakar Dam was produced as a normal model with a horizontal scale of 1/25 and a vertical scale of 1/25. The equipment that are used during testing process are Nixon Streamflo Velocity Meter and Ultrasonic Flow Meter. Nixon Streamflo Velocity Meter can measure the velocity of water from the opening of the radial gate while Ultrasonic Flow Meter can measure the discharged from the pipe during the physical model was running. To know the accuracy of this testing equipment, the calibration testing was done before use it during the testing process on physical model. The result from the testing process show the discharge coefficient and the relationship of discharge (m3/s) with the upstream head (mm) of reservoir at difference opening of the radial gate. From this physical model testing, discharge coefficient (Cd) from all radial gates are between 0.75-0.84. Besides that, for the full-scale physical model, opening of 0.5m, 0.65m, 0.5m for all radial gate show the highest discharge which is 417 m3/s. This will help TNB in process to release water from SAB Dam to avoid occurrence of flooding.